The impact of air pollution control measures and the COVID-19 pandemic on photosynthesis in urban trees - Takumi Matsuura; Yousuke Okamoto; Mayu Matsumoto; Takashi Kiyomizu; Luisa Kumpitsch; Atsushi Kume; Yuko T. Hanba (Scientific Reports)
Abstract Phytotoxic air pollutants such as atmospheric nitrogen dioxide (NO2) are among the major stresses affecting tree photosynthesis in urban areas. We clarified the relationship between NO2 concentrations and photosynthetic function for three major urban trees, Prunus × yedoensis, Rhododendron pulchrum, and Ginkgo biloba, planted in Kyoto and surrounding cities, combining our published data and new data collected from 2020 to 2023. High NO2 increased long-term water use efficiency for all species. High NO2 decreased photosynthesis in P. yedoensis and R. pulchrum, while for G. biloba, NO2 imposed little effect on photosynthesis. We then focused on the decrease in NO2 due to (1) air pollution control measures from 2005 to 2023 and (2) the economic recession caused by the COVID-19 pandemic, and examined whether these factors improved photosynthesis in urban trees. The historic decrease in NO2 improved leaf photosynthesis for P. yedoensis and R. pulchrum, while the COVID-19 pandemic reduced NO2 by only 0.3 ppb and did not further improve photosynthesis in these tree species. This report shows that air pollution control measures improved photosynthesis in urban trees over several years in Japan, and is valuable because it demonstrates that air pollution control measures can increase CO2 uptake by urban trees.